Addition of mental health to the lady health worker curriculum in Pakistan: now or never - Fauziah Rabbani; Samina Akhtar; Javeria Nafis; Shahid Khan; Sameen Siddiqi; Zul Merali (BMC, 2023)
Abstract The technical advisory group of the World Health Organization (Geneva, Switzerland) has suggested person-centered and community-based mental health services in response to the long-term and far-reaching mental health impacts of the COVID-19 pandemic. Task shifting is a pragmatic approach to tackle the mental health treatment gap in low- and middle-income countries. Pakistan is dismally resourced to address the mental health challenges. Pakistan's government has established a lady health worker's program (LHW-P) which can be effectively utilized to provide some basic mental health services at community doorsteps. However, lady health workers' current curriculum does not include mental health as a subject. WHO's Mental Health Gap Intervention Guide (mhGAP-IG) Version 2.0 for mental, neurological, and substance use disorders in non-specialist health settings can be adapted and utilized to be included as part of the LHW-P curriculum in Pakistan. Thus, the historical lack of access to mental health support workers, counsellors, and specialists can be addressed. Additionally, this will also help to reduce the stigma associated with seeking mental health care outside the boundaries of home, mostly at a huge cost.